Ethanol extract of mangosteen peel reduces histological count of alveolar macrophage and pulmonary alveolar space size in male white rats (rattus norvegicus) exposed to cigarette smoke - Santoso, Anna Lewi (Folia Medica Indonesiana, 2016)
This study aims to analyze histological alveolar macrophage cell number and width of pulmonary alveolar space white male rats given ethanol extract of mangosteen peel and then exposed to cigarette smoke. Smoking can reduce antioxidant and increases free radicals, so it is recommended increasing the antioxidants found in many mangosteen rind. This research was an experimental laboratory using the randomized post test-only control group design. White rats male were chosen randomly into 5 groups (K1, K2, P1, P2, P3). K1 (control-), only the Na-CMC 0.5%, K2 (control+) given Na-CMC 0.5% solution and smoke, P1, P2, P3 given the ethanol extract of mangosteen rind (50, 100, and 200mg/kg wt) and smoke. The data were tested normality and homogenity. Then they were analyzed with one-way Anova, LSD. Data that are not normally tested with Robust tests – (Brown-Forsythe) and Tamhane's. Correlation test with Pearson and Spearman. Robust test results, the number of alveolar macrophages, value p=0.000 (p